Annellophora catenata sp. nov. from India - D.K. AGARWAL and I.K. KUNWAR, C. MANOHARACHARY, N.K. RAO (Indian Phytopathology, 2005)
A new species of Annellophora is proposed with conidiophores arising in groups of 2-4, percurrent proliferations 2-4, uniform in their structure; both primary and secondary conidia almost identical in their morphology viz. size, shape and number of septa. The taxon named as Annellophora catenata sp. nov., specific epithet indicating the catenate nature of the conidia.